Multicenter investigation of moral distress among physicians and its impact on the intention to leave working position (International Journal of Occupational Safety and Health, 2024)
Introduction: The evidence concerning Moral Distress (MD) among physicians is limited, while such data are absent for physicians working in the Greek National Health System (GNHS). The purpose of this study is the investigation of MD among physicians in Greece and the validation Moral Distress Scale-Revised (MDS-R) as a reliable method for the measurement of MD in the Greek language.Methods: This is a multicenter study in which 200 physicians of all specialties and degrees participated. A self-reporting questionnaire was used. The MDS-R questionnaire is constituted of 21 items that describe conditions met in clinical practice, aiming to investigate the frequency and intensity of such cases. The questionnaire was translated and validated in the Greek language.Results: The test-retest procedure was undergone in a sample of 18 physicians and it was found significant and high agreement in all of the MD scale items. Therefore, all 21 items of the MDS-R questionnaire were found suitable for inclusion in the Greek version of MDS-R. A model of four main factors emerged after the analysis of the results with a total variance of 46,8% and all these factors were correlated with each other. MD was detected to a significant degree in more than half participants. The incidence and intensity of MD were higher in physicians who worked in general hospitals compared to those working in cancer hospitals, which is reported for the first time.Conclusions: The Greek version of MDS-R is a valid and reliable instrument for the investigation of MD among Greek physicians. Moral distress impacts the Greek physicians but the degree depends on the working position. Moral distress is also associated with leaving a working position among Greek physicians.